Acute Respiratory Infection (ARI) in children in Ethnic Minority Communities of Chittagong Hill Tracts, Bangladesh: A qualitative study - Maidul Alam Chaklader (Journal of Health and Social Sciences)
Introduction: The Chittagong Hill Tracts (CHT) region of Bangladesh, home to 11 distinct ethnic minority communities, has been disadvantaged and isolated for many years due to 25 years of insurgency and political turmoil. This area has higher child mortality rates than the national average. This study attempts to explore a holistic understanding on the ways that Acute Respiratory Infections (ARIs) are understood and managed in the CHT. Methods: An ethnographic approach based on participant observation coupled with semi-structured interviews, key informant interviews and focus groups has been used. The notion of Explanatory Models (EMs) encompassing concepts such as local aetiology and terminologies, treatment-seeking behaviour, illness experience, symptom recognition and reporting held by local communities has been employed as a conceptual framework. Results and Discussion: The study findings indicate that EMs for childhood ARI varied within and across ethnic groups. Study participants tended to integrate both physical and supernatural causes into their EMs. Despite the widespread tendency to consider folk beliefs in binary opposition to biomedical causes, findings from this study show that both consider proximate and underlying factors related to childhood ARI and many of these underlying factors that render children more susceptible to ARI are actually common to both models. Treatment-seeking behaviour is a complex process represented by shifting interpretations of the illness and treatment options and constrained by poverty and other structural factors that set the context in which study participants operate on a daily basis. Conclusion: Researchers and policy-makers need to employ a more expansive concept of EMs that accommodates the mundane struggles and involuntary aspects of health care and treatment-seeking behaviour of individuals from marginal communities all over the world and should subsequently move away from the simplistic idea that exotic beliefs and practices of local communities are ‘cultural barriers’ to effective health care.